The relationship between reading in L1 and EFL writing performance / Rahmah Mohd Rashid - Mohd Rashid, Rahmah (Institute of Research, Development and Commercialization (IRDC), 2007)
Earlier studies on reading and writing relationship have shown that what is learned in reading changes as students come to terms with the process (Chall, 1996). Beginning readers are much more word bound or word oriented than those who are proficient readers and writers. As readers develop a comfortable grasp of basic word recognition and spelling, their attention begin to shift to other issues of interpretation and communication. The developmental lines of reading and writing, according to Shanahan, (1997), are sufficiently similar that the two activities can be combined successfully, in different ways, throughout literacy education.